A Polymeric Extracellular Matrix Nanoremodeler for Activatable Cancer Photo‐Immunotherapy. Issue 12 (10th February 2023) - Zhang, Chi; Xu, Mengke; Zeng, Ziling; Wei, Xin; He, Shasha; Huang, Jingsheng; Pu, Kanyi
Abstract: Cancer immunotherapy has shown tremendous potential to train the intrinsic immune system against malignancy in the clinic. However, the extracellular matrix (ECM) in tumor microenvironment is a formidable barrier that not only restricts the penetration of therapeutic drugs but also prevents the infiltration of antitumor immune cells. We herein report a semiconducting polymer‐based ECM nanoremodeler (SPNcb) to combine photodynamic antitumor activity with cancer‐specific inhibition of collagen‐crosslinking enzymes (lysyl oxidase (LOX) family) for activatable cancer photo‐immunotherapy. SPNcb is self‐assembled from an amphiphilic semiconducting polymer conjugated with a LOX inhibitor (β‐aminopropionitrile, BAPN) via a cancer biomarker (cathepsin B, CatB)‐cleavable segment. BAPN can be exclusively activated to inhibit LOX activity in the presence of the tumor‐overexpressed CatB, thus blocking collagen crosslinking and decreasing ECM stiffness. Such an ECM nanoremodeler synergizes immunogenic phototherapy and checkpoint blockade immunotherapy to improve the tumor infiltration of cytotoxic T cells, inhibiting tumor growth and metastasis. Abstract : A semiconducting polymer‐based extracellular matrix (ECM) remodeler (SPNcb) with photodynamic antitumor activity and inhibition of collagen‐crosslinking enzymes is developed for activatable cancer photo‐immunotherapy. SPNcb‐mediated ECM‐remodeling therapy synergizes with checkpoint blockade immunotherapy to reinvigorate cytotoxic T cell‐mediated antitumor immunity, inhibiting tumor growth and metastasis.